The global future of English studies - English, James F., 1958- (Hoboken, N.J. : John Wiley & Sons, 2012)
The Global Future of English Studiespresents a succinct, carefully documented assessment of the current state and future trajectory of English studies around the world.Compiles data on student enrollments, faculty hiring, and financing in English studies around the world including China, home to more English majors than the U.S. and U.K. combinedRejects prevailing narratives of contraction and decline that dominate histories of the disciplineStresses English studies' expansion within a rapidly expanding global academic apparatus, and the new challenges and opportunities such sudden and dispers.
Front Matter -- PART I: The Future of English Enrollments -- PART II: The Future of English Professors -- PART III: The Future of the English Curriculum -- Manifesto -- Index.
Includes index.
Print version record.
Keywords: English language -- Study and teaching; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; English language -- Study and teaching; Electronic books